Pathological and Immunohistochemical Features of Malignant Peripheral Nerve Sheath Tumor With Heterologous Rhabdomy Oblastic Differentiation (Malignant Triton Tumor) in the Context of the Malignant Peripheral Nerve Sheath Tumor Spectrum - Arias-Ruiz, Luis Felipe; Ortíz Hidalgo, Carlos Federico (SAGE Publications, 2025)
Malignant peripheral nerve sheath tumors (MPNST) are aggressive sarcomas arising from Schwann cells or neurofibromas, comprising ∼10% of soft tissue sarcomas. Found in 8% to 13% of neurofibromatosis type 1 patients, they typically show spindle cells expressing S100 and SOX10. Some display heterologous differentiation (bone, cartilage, vessels, or glands). When rhabdomyosarcomatous features are present, they are called malignant peripheral nerve heath tumor with heterologous rhabdomyoblastic differentiation (malignant triton tumors), which are more prone to recurrence, metastasis, and worse outcomes. Epithelial differentiation does not affect prognosis. Despite advances in understanding MPNST biology, many pathophysiological mechanisms remain unclear. This review highlights their histopathology, focusing on malignant triton tumor. ©The authors ©SAGE.
Keywords: Pathological; Immunohistochemical; Malignant Peripheral Nerve